An assessment of the perceptual elements of urban streets based on the context of urban tourism - The case of Sheffield - Huang, Siqi (Frontiers in Public Health, 2024)
After COVID-19, more and more travelers are more inclined to walk in cities, and the sensory elements of streets can have a significant impact on urban tourism. Residents and travelers have different perceptions of the street and preferences for its use. The purpose of this study is to evaluate and analyse the streets from the perspective of locals and travelers, in the hope that it can provide some data for future urban management and designers to learn from and refer to for the improvement and renewal of streets. In this study, a questionnaire was designed to obtain residents' and travelers' evaluations of the sensory elements of the street and a quadrant analysis of the street's sensory elements was carried out using the IPA-Kano model. The results of the study show that travelers are particularly concerned about maps and signage guidance, while residents are more concerned about the green environment of the surroundings and how well it is maintained.